Assessing the effects of anthropogenic stressors on Puget Sound flatfish populations - Johnson, Lyndal L.; Landahl, John T.; Kubin, Leslie A.; Horness, Beth H.; Myers, Mark S.; Collier, Tracy K.; Stein, John E. (Journal of sea research, 1998)
Puget Sound is an estuary in the northwestern United States which serves as the habitat for a number of recreationally and commercially important species of flatfish. Over the past 100 years, there has been substantial urban and industrial development within this region, resulting in heavy inputs of chemical contaminants at selected sites, as well as significant loss or alteration of marine habitat. Studies show that feral flatfish in Puget Sound are experiencing a range of biological effects due to chemical contaminant exposure, including reproductive dysfunction, altered immune competence, and development of toxicopathic diseases, and there is some evidence of reduced survival in fish from urban areas of Puget Sound from increased infectious and toxicopathic disease. Puget Sound sole are also subject to other anthropogenic stressors, such as fishing pressure or alteration of nearshore nursery habitats. The cumulative impact of these stressors on flatfish abundance in Puget Sound, however, is poorly understood. In a series of field and laboratory studies, we determined vital rates and other life history parameters in English sole ( Pleuronectes vetulus) subpopulations from urban and non-urban sites in Puget Sound, and are using this information to estimate potential population level impacts of anthropogenic stressors, with age and stage-based Leslie-matrix models. Initial results suggest that declines in the fecundity component of the model, as observed in field studies of fish from contaminated sites, could reduce the size of sub-populations in these areas if the loss of recruits is not offset by density-dependent changes in recruitment, immigration, or other compensating mechanisms. Studies on flatfish species from a variety of sites in Europe and North America suggest that contaminant-related disease and reproductive impairment are widespread in this group of fish, although substantial differences in sensitivity have been observed, even among closely related species. Comparative studies with a variety of Pleuronectid species will enable us to better evaluate the risk posed by anthropogenic stressors to flatfish, and contribute to improved assessment and management of this important fisheries resource.